Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Mobil Daihatsu Grand Max Pick Up (Studi pada PT. Astra International Tbk Daihatsu Cabang Malalayang) - Igir, Friani Gloria; Tampi, Johny R. E.; Taroreh, Henny (Sam Ratulangi University, 2018)
The purpose of this study is to determine the effect of product quality and price to the decision of the purchase of grand max pick up car. Purchase decision is a consumer's decision to buy a product after previously thinking about whether or not worth buying the product by considering the information he knows with the relitas about the product after he witnessed it. The method used in this research is quantitative descriptive method, with the approach of Multiple Correlation Analysis and Multiple Linear Regression to measure the relationship between variables. This research was conducted at PT. Astra International Tbk Daihatsu Malalayang branch, with the object of research is Daihatsu Gran Gran Pick Up. Based on the result of validity test show indicator of variable of product quality, price and purchase decision of correlation value bigger. While the results of multiple linear analysis shows all variables ranging from products and prices have a positive influence on purchasing decisions. The coefficient of determination showed that 77% of Daihatsu Gran Max Pick Up's car purchase decision at PT. Astra International Tbk Daihatsu Malalayang branch is influenced by variables such as product and price. Based on the results of the discussion then found the quality of products and prices have a significant effect on purchasing decisions. Each variable has a significant positive effect on the purchasing decision.